EFFECT OF EDUCATIONAL BACKGROUND AND WORK EXPERIENCE ON COUNSELOR’S WORK ENGAGEMENT - Rahman, Fathur; Aminah, Siti; Nurmalasari, Yuli (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
Work engagement serves as one of the dimensions contributing to the development of professional identity. This article aimed to describe the level of work engagement of school counselors, and the influence of work experience and educational background on counselors' work engagement. To this end, this comparative study involved school counselors as participants of the study, recruited using an incidental sampling technique. The participants were asked to share the invitation link to several school counselor social media groups in Indonesia. A work engagement scale adapted from the Utrecht Work Engagement Scale was employed to collect the data. The data were analyzed by inferential statistics using two-way ANOVA. The result shows that the average work engagement of participants was categorized as high. It was also found that work experience and educational background did not affect counselors' work engagement. The results of this study serve as preliminary findings of a complete framework for further research on the professional identity of school counselors in Indonesia.